Synthesis of 1,2,4-Oxadiazoles via DDQ-Mediated Oxidative Cyclization of Amidoximes - Parker, Patrick D.; Pierce, Joshua G. (Synthesis, 2016)
An oxidative cyclization of amidoximes to form 1,2,4-oxadiazoles, mediated by 2,3-dichloro-5,6-dicyano-1,4-benzoquinone (DDQ), is described. A range of alkyl, aryl, and heteroaryl substrates are tolerated under these conditions. This reaction serves as an alternate approach for the synthesis of functionally diverse oxadiazoles via a rapid and straightforward synthetic procedure.
Keywords: oxidation; cyclization; heterocycles; radicals; medicinal chemistry